Shared Histories of Co-evolution May Affect Trophic Interactions in a Freshwater Community Dominated by Alien Species - Haubrock, Phillip J.; Balzani, Paride; Azzini, Martina; Inghilesi, Alberto F.; Veselý, Lukáš; Guo, Wei; Tricarico, Elena (Frontiers in Ecology and Evolution, 2019)
Interactions occurring between species in multiple invaded freshwater ecosystems are often difficult to observe and study. Studies on invasive alien species typically focus on single species, and, when the species community is exclusively composed of alien species, their interactions, eventual facilitation and hindering processes are very scarcely assessed. To investigate such a community, the species community in the Arno River (Tuscany, Italy) was examined as a model system using the combined approach of stable isotopes and dietary analyses. Established alien species have formed a pyramid shaped community with the European catfish Silurus glanis and the North American channel catfish Ictalurus punctatus in the apex position, followed by opportunistic predatory (Lepomis gibbosus) and omnivore (Alburnus alburnus, Cyprinus carpio, Barbus barbus, Pseudorasbora parva, Padogobius sp., Tinca tinca) species. These species were observed to feed on a variety of primary producers (Myriophyllum sp., Potamogeton sp., Phragmites australis) and consumers (aquatic insects, molluscs, Dikerogammarus villosus, Procambarus clarkii, Palaemon antennarius, tadpoles). Remarkably, the channel catfish Ictalurus punctatus showed an ontogenetic niche shift, with juveniles occupying a slightly higher trophic position than mature individuals. Pseudorasbora parva and A. alburnus showed a strong niche overlap, with the former having a wider niche. Such wide niches were also found for the invasive crustaceans D. villosus and P. clarkii. Outgoing from our findings, we suggest that life-history and geographic origin play a role in determining competition and interaction type among alien species, with species from the same geographic area showing a lower potential to compete than species from different areas, hence affecting their potential impact on native species.